ANALISA FAKTOR mA PADA PESAWAT X-RAY GENERAL MERK ALLENGERS TYPE 325 - Yusalim Azis; Samser Nababan (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2019)
The analysis of the mA factor has been carried out on the X-Ray General aircraft brand Allengers type 325 which was carried out in the radiology laboratory of the Sari Mutiara Indonesia University. The problem is finding the mA accuracy by making a factor of 50 mA, 100 mA, 150 mA, 200 mA. The aim is to determine and analyze the level of accuracy of x-ray accuracy and film density.The research method used is quantitative research methods through measurement and data collection directly on the X-Ray General Allenger brand type 325, the results of the data obtained were analyzed descriptively using tables and graphs.Current accuracy (mA) measurements were carried out four times using variations of ma, including 50 mA, 100 mA, 150 mA, 200 mA, and using a voltage of 50 kV and a time of 0.25 S, and using FFD with a height of 100 cm. Good measurement results are using a capacity of 50 kV, 100 mA, 0.25 S on the X-Ray General aircraft brand Allengers type 325 which is in the radiology laboratory of Sari Mutiara Indonesia University. Key words: general x-rax, diagnostic